1995
DOI: 10.1093/ndt/10.4.527
|View full text |Cite
|
Sign up to set email alerts
|

The value of different resistance parameters in distinguishing biopsy-proved dysfunction of renal allografts

Abstract: Abstract. The data concerning the value of duplex sonography in diagnosing parenchymatous renal allograft dysfunction are controversial. Most early studies did not take into consideration the many factors influencing resistance parameters. We therefore performed a prospective, biopsy-controlled study with exclusion of all known sources of error regarding resistance parameters. Furthermore we investigated the value of a new resistance parameter, the systolic deceleration percentage. Forty-seven duplex sonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…PSV is a quantitative index that depends directly on the systolic jet, heartbeat and blood pressure. This parameter also seems strongly influenced by the general condition of the renal microcirculation, therefore it is not useful for defining specific allograft problems [12,13]. In the present study PI yielded results similar to RI.…”
Section: Discussionsupporting
confidence: 43%
“…PSV is a quantitative index that depends directly on the systolic jet, heartbeat and blood pressure. This parameter also seems strongly influenced by the general condition of the renal microcirculation, therefore it is not useful for defining specific allograft problems [12,13]. In the present study PI yielded results similar to RI.…”
Section: Discussionsupporting
confidence: 43%
“…The extensibility or elasticity of the vessel decreases with age and with any associated cardiovascular risk factors, whereas the related peripheral resistance increases as an expression of the arteriosclerosis. 12,17,20 Before the appearance of morphological alterations that are detectable from the thickening of the intima-media complex, the early form of arteriosclerosis leads to endothelial dysfunction as an exclusively functional disorder. Even at this stage, it is already associated with increased cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects local wall extensibility and the related vascular resistance. 1,12,13 There is a clear correlation between increasing RI values and arteriosclerosis risk factors and manifestations. 14 -16 In the renal arteries, RI has also been shown to have prognostic value for revascularization in renovascular hypertension.…”
mentioning
confidence: 99%
“…Duplex Doppler sonography is useful for detecting intrarenal hemodynamic abnormalities such as those seen in obstructive renal diseases and renal allograft rejection (8,9). We previously demonstrated that resistive index (RI) measured by duplex Doppler sonography is useful for demonstrating hemodynamic abnormalities present in diabetic nephropathy (10,11).…”
mentioning
confidence: 99%